Characteristics and effects of phototherapy in newborn: integrative review (Research, Society and Development, 2021)
This study aims to analyze the scientific evidence about the characteristics and effects of phototherapy in newborns. This is an integrative literature review, carried out in databases of Latin American and Caribbean Health Sciences Literature (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Web of Science, with search strategies with Health Sciences Descriptors (DECS) and Medical Subject Headings (MeSH). Nineteen articles between 2011 and 2019 were selected for analysis, based on the review question and inclusion criteria. The analysis of the studies revealed as one of the scientific evidences, the types of phototherapy: conventional, light emitting diode (LED), double LED, continuous and intermittent. The other evidence found was the effects and uses of phototherapy, such as: heart rate variability, oxidative stress, decreased serum globulin, hypocalcemia, epilepsy, increased metabolites. Phototherapy is beneficial because it degrades serum bilirubin, preventing complications such as kernicterus. However, its indiscriminate use should be reviewed and its use needs to be careful to avoid the realization of phototherapy sessions if bilirubin has not reached the recommended levels. Thus, it is emphasized that nursing acts in care of the newborn in phototherapy and need to have their practice based on scientific evidence, since it qualifies and humanizes care based on biopsychosocial needs. In addition, this qualification allows the best choice of assistance to the newborn and his family.